(3GdebGeGJ GdRjfjIs - (3eYO Hf fUQ Gddg Hf QLH, CHh GdfOj TeS GdOjf GHf CHj GdaJM, GdeYQha HGHf GdUjbd GdLRQj,J (B701 (3g` s ((3eMeO Hf eMeO Hf eMehO Hf eMeO Hf MSf Hf eMeO Hf YQHi Gdabjg GdMfai s)
(3ChdgG (B:s
(3EYde CjOc Gddg JYGdi Cfg bO jQO Ydjc ai cJGHfG gPG daXI PGJ dZJjf aUGYOkG aEf cGfJ PGJ dZJjf adGjNdh ef Cf Jchf GddZJGf eJSGhjJjf ai GdaUGMI Ch GdhGMOI QGLMI hGdCNQi eQLhMI s
(3BNQgG (B:s
(3hSeY GdSjO GdEeGe TgGH GdOjf MSjf Hf bJGOg GdeOfi ef Chd GdcJGH Edi BNQ GdebGeI GdCQHYjf hgh BNQ GdeLdS GdKGef MGeOkG ddg Ydi fYeg heUdjkG Ydi NjQ Ndbg eMeO hBdg hUMHg hYJQJg heSdekG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B304 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B465s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1785s
Keywords: (3GdCOHs